Structure and IR Spectra of 3(5)-Aminopyrazoles and UV-Induced Tautomerization in Argon Matrix - Secrieru, Alina (2021)
The prototropic tautomerism in 3(5)-aminopyrazoles was investigated by matrix isolation infrared (IR) spectroscopy, supported by DFT(B3LYP)/6-311++G(d,p) calculations. In consonance with the experimental data, the calculations predict tautomer 3-aminopyrazole (3AP) to be more stable than the 5-aminopyrazole (5AP) tautomer (calculated energy difference: 10.7 kJ mol-1; Gibbs free energy difference: 9.8 kJ mol-1). The obtained matrix isolation IR spectra (in both argon and xenon matrices) were interpreted, and the observed bands were assigned to the tautomeric forms with help of vibrational calculations carried out at both harmonic and anharmonic levels. The matrix-isolated compound (in argon matrix) was then subjected to in situ broadband UV irradiation (λ > 235 nm), and the UV-induced transformations were followed by IR spectroscopy. Phototautomerization of the 3AP tautomer into the 5AP form was observed as the strongly prevalent reaction.